Novel Pathways to Erythropoiesis Induced by Dimerization of Intracellular C‐Mpl in Human Hematopoietic Progenitors123. (22nd March 2012) - Parekh, Chintan; Sahaghian, Arineh; Kim, William; Scholes, Jessica; Ge, Shundi; Zhu, Yuhua; Asgharzadeh, Shahab; Hollis, Roger; Kohn, Donald; Ji, Lingyun; Malvar, Jemily; Wang, Xiaoyan; et al.
Abstract: The cytokine thrombopoietin (Tpo) plays a critical role in hematopoiesis by binding to the extracellular domain and inducing homodimerization of the intracellular signaling domain of its receptor, c‐Mpl. Mpl homodimerization can also be accomplished by binding of a synthetic ligand to a constitutively expressed fusion protein F36VMpl consisting of a ligand binding domain (F36V) and the intracellular signaling domain of Mpl. Unexpectedly, in contrast to Tpo stimulation, robust erythropoiesis is induced after dimerization of F36VMpl in human CD34+ progenitor cells. The goal of this study was to define the hematopoietic progenitor stages at which dimerization of intracellular Mpl induces erythropoiesis and the downstream molecular events that mediate this unanticipated effect. Dimerization (in the absence of erythropoietin and other cytokines) in human common myeloid progenitors and megakaryocytic erythroid progenitors caused a significant increase in CD34+ cells ( p < .01) and induced all stages of erythropoiesis including production of enucleated red blood cells. In contrast, erythropoiesis was not seen with Tpo stimulation. CD34+ cell expansion was the result of increased cell cycling and survival ( p < .05). Microarray profiling of CD34+ cells demonstrated that a unique transcriptional pattern is activated in progenitors by F36VMpl dimerization. Ligand‐inducible dimerization of intracellular Mpl in human myeloerythroid progenitors induces progenitor expansion and erythropoiesis through molecular mechanisms that are not shared by Tpo stimulation of endogenous Mpl. STEM CELLS 2012; 30:697–708